Grammatical Cohesive Device Analysis of Reading Text in English Text Book for 7th Grade Students of Junior High School - Lailatul Qadar; Safnil Arsyad (Jambura Journal of English Teaching and Literature, 2026)
Cohesive devices can pose problems for junior high school students in reading English passages when they are not aware of them; this is why they should know the devises and how they are used in the reading passages. This study aims to analyze the use of Grammatical cohesive devices in reading text in New Frontiers 1, an English text book for seventh grade of Junior High School’s students. Using Qualitative descriptive content analysis, this study used ten reading texts from ten chapters of the book as its data source. The analysis is based on the cohesion framework proposed by M. A. K. Halliday and Ruqaya Hasan which categorizes grammatical cohesion into reference, substitution, ellipsis, and conjunction. All of the texts were analyzed based on their types, functions, and the variety level of grammar cohesive devices used. The finding of this study shows that reference and conjunction are the most dominant used grammar cohesive device. Personal reference functions to maintain the subject identity and the information continuity in text. Conjunction, especially the additive and temporal conjunction, helps building a logically coherent idea. On the contrary, Ellipsis and substitutions appear in a limited number. This finding indicate that the texts in the book are mainly written for beginner English learners. It makes the grammar cohesive devices used are simpler and more explicit, matches the character of beginner learners who use this book as learning source. The result also implies the importance of developing teaching material which gradually introduces cohesive device in learning English on Junior High School level.